The triple condition of Unamuno's God: between the cordial belief, the agonizing doubt, and the atheism of God - Ledesma de la Fuente, Álvaro (Pensamiento. Revista de Investigación e Información Filosófica, 2026)
Unamuno's conception of God is framed by the interaction between belief, doubt, and atheism, challenging the conventional categories of the existence of God by presenting it as a reflection of his personal struggle between faith and reason. This article offers three proposals to understand the figure of the Unamunian God: first, as a believed God, a divinity whose existence is assumed and affirmed; second, as a created God, shaped by the faith placed in him by his believers; and lastly, as an atheist God, whose existence implies his negation. These observations demonstrate the complexity of Unamuno's theory with the divine and illustrate his thoughts on the nature of divinity.
Keywords: Unamuno; God; Agnosticism; Atheism; belief; creation